Constructions with Evaluative Genitive Adnominal as Means of Axiological Marking - T. M. Shkapenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
Constructions with adnominal evaluative genitive are considered as a specific way of encoding the axiological scores on the morphosyntactic level. The linguo-axiological approach to the study of this construction indicates the novelty and relevance of the study. Constructions of type “N nom. + N gen.” in which the position of subject is taken by the noun man or anthroponymic nouns are selected as the main object of study. It is proved that the coding of axiological evaluation in the framework of this syntactic model is based on the implementation of two main types of possessiveness: possession and belonging. The dependence of the character and intensity of evaluation on the semantic-syntactic structure of the combination is established. Inverted constructions like man of honor in which the characteristic property acquires the status of an inalienable value, and the subject itself acts as its reference carrier are described as having the greatest axiological potential. The authors claim that positive attitude in converses determines their functioning in the role of prescriptive linguistic concepts or ideologemes. It is noted that the smaller axiological potential within the estimative polarity is inherent in constructions with a figurative meaning of possessiveness, in which the assessment of a person occurs by indicating his belonging to the place, time or occupation ( man of the era , man of the year , man of show business ).